Values in Modern Javanese Songs and Their Relevance to Character Education: A Cultural Semiotics Study - Mardiyansyah, Mardiyansyah; Sulanjari, Bambang; Werdiningsih, Yuli Kurniati (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2024)
Modern Javanese songs (tembang Jawa modern) represent a product of cultural negotiation that combines traditional aesthetics with contemporary expressions. This study aims to analyze the semiotic values embedded in modern Javanese-language songs and their relevance to character education in the digital era. Employing Roland Barthes' cultural semiotics approach integrated with critical discourse analysis, this study decodes the signs, myths, and ideologies inscribed within song lyrics. Research data derive from a corpus of modern Javanese songs documented in prior scholarly works, encompassing compositions by musicians such as Didi Kempot, Ndarboy Genk, and Guyon Waton. The analysis proceeds through three stages: identification of denotative signs, deconstruction of connotative meanings, and reading of cultural myths. Findings reveal that modern Javanese songs encompass four principal value strata: religio-sufistic values, moral-ethical values, social-humanistic values, and cultural-identity values. These values are manifested through complex linguistic and paralinguistic sign systems, positioning modern Javanese songs as a potentially effective medium for character education when systematically integrated into educational curricula. This study contributes to the development of a contextually grounded, local-wisdom-based learning model relevant to millennial learners.